Guidance And Counseling : The Integration Of Religion And Science In 21st Century For Character Building - Firman Mansir; Syarnubi Syarnubi (At-Tarbiyat, 2021)
The implementation of the education sector in Indonesia is currently facing some problems. The learning process seems unclear and far from real life. Thus, students find it difficult in understanding the values in learning a subject. Indeed, this indicates the low quality of education in schools. This research is qualitative with data collection methods through documentation and literature review from various primary and secondary data. The findings of this study indicate that the learning process in contextualization is conducted by integrative learning. Integrative learning can be applied with topics about a discourse discussed from various points of view, and disciplines are interrelated and overlapping. In addition to creating effectiveness in integrative learning time, it also creates a direct experience. Therefore, students can add strength to accept, store, and apply the concepts that have been learned. This research implies that Integrative learning also helps students learn completely and meaningfully, not only by understanding and memorizing it. Thus, it is easily applied by students in everyday life. Research from a school that uses the concept of a natural school that applies integrative learning in all subjects gave rise to the author's curiosity about the implementation of integrative learning in the school.